Analysis of Academic Self-Efficacy Levels of University Students Doing Sport Regularly and those Not Doing Sport Regularly - Ermiş, Egemen (Asian Journal of Education and Training, 2019)
The purpose of this study is to analyze academic self-efficacy levels of university students studying in different departments according to their states of doing regular sports and some variables. 299 students, 153 females and 146 males, studying in different departments of Samsun Ondokuz Mayıs University participated in the study voluntarily. “Academic Self-efficacy Scale” which was developed by Owen and Froman (1988) and adapted to Turkish by Ekici (2012) and which included 33 questions and 3 sub-dimensions (social status, cognitive practices, technical skills) was used in the study to find out academic self-efficacy levels of students in terms of different variables. SPSS 22.0 program was used for statistical analysis. When the results were analyzed, statistically significant difference was found only in social status sub-dimension in terms of the variables of gender and grade (p<0.05). No significant difference was found in other sub-dimensions for both variables (p>0.05). When academic self-efficacy levels were analyzed in terms of students’ states of doing regular sports, statistical significance was not found in any of the sub-dimensions (p>0.05). As a conclusion, it was found that the state of doing sports regularly did not have an influence on academic self-efficacy level. This result is thought to occur due to the fact that the experimental group in the present study does not consist of only students from the faculty of sport sciences, but also from students studying in different departments of the university.